Financial systems, markets and institutional changes - Lindblom, Ted; Sjögren, Stefan; Willesson, Magnus (New York Palgrave Macmillan, 2014)
Analyses and exemplifies how the financial system endogenously adjusts to institutional changes and puts particular emphasis on how different institutional settings affect firms' borrowing and how the financial crisis affected the relationship
Includes bibliographical references and index.
oif 12/06/15
Loan
Keywords: Financial institutions; International finance; Monetary policy